THE FUTURE OF THE CRYPTOCURRENCY MARKET - A. Berdyshev (Publishing House of the State University of Management, 2018)
The history of creating bitcoin cryptocurrencies has been considered, the main features of cryptocurrencies and cryptocurrency market have been identified. Based on the identification of features of the blockchain technology, the possibilities of making settlements outside the traditional financial system have been determined. Special attention has been paid to the issue of legal regulation of cryptocurrency in various countries. According to the results of a study of current trends in the cryptocurrency market, in the conditions of a significant decline in the market value of bitcoin in 2018, as the flagship of the cryptocurrency market, prospects for its development have been determined